Evaluasi Program IKD (Identitas Kependudukan Digital) Dalam Mendukung Sistem Government di Kecamatan Kenjeran Kota Surabaya - Julia Kartika Eksaputri; Lingga Nurwidyasari; Rachel Valentina; Oktarizka Reviandani (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In population administration public services, the government is now adopting e-government-based innovations such as Digital Population Identity (IKD) which includes digitization of population documents including E-KTP. Through the activation of IKD, residents can access their personal data in electronic form, utilize in formation and communication technology, increase the use of digitization, accelerate digital public or private services, and ensure the security of IKD ownership. The implementation of IKD is led by the Director General of Population Administration with the assistance of local governments at various levels, for example Surabaya City where the Dispendukcapil works with the government at the Kenjeran Sub-district level. The evaluation of the IKD program in Kenjeran sub- district followed the steps of Isaac and Michael's 1984 program evaluation theory, from formulating questions and information needs, to presenting data to decision makers. The research was conducted in a descriptive qualitative man nearby utilizing interviews, observation, and documentation as primary and secondary data collection techniques. The results of the analysis show that Kenjeran Sub-district has succeeded in carrying out its duties effectively, but needs to increase socialization and education to the community so that the implementation of Digital Population Identity can run smoothly and provide maximum benefits to the community. Keywords: E-Government, Evaluation, Digital Residence Identity.